A scoping review of the prevalence of musicians’ hearing loss - Firle, Carl; Richter, Antonia Helen (Frontiers in Public Health, 2025)
IntroductionHearing loss is the most commonly recognized occupational disease in Germany. Musicians are also affected, as playing classical music can expose them to high or very high sound volumes. With this scoping review, we aimed to assess the prevalence of noise-induced hearing loss among professional musicians and evaluate its characteristics.MethodsThe databases such as MEDLINE, Embase, Cochrane Library, and Google Scholar were searched using the terms (hearing loss OR hearing impairment OR hearing difficulties OR acoustic trauma) AND (musician) on 14 August 2023 and 2 January 2025. Only original studies with audiometric examination results were included.ResultsA total of 79 studies were retrieved for descriptive analysis. The median number of participants was 52 (IQR 30-109). The majority of the retrieved studies included participants with at least 5 years of experience as practicing musicians. The proportion of men was significantly higher than that of women, with the medianmen portion of 69% (IQR 53–83%). Students were a common study population, indicating that the data on older and retired musicians were either rare or missing. As a result, the lifetime prevalence of hearing loss in musicians could not be determined. The data analysis showed an increased risk of hearing loss >15–20 dB in the frequency range of 4,000–6,000 Hz among participants in the classical genre group. Studies with participants having normal hearing were also found within that genre. Rock, pop, and jazz musicians had an increased risk of hearing loss >20 dB in the frequency range of 3,000–8,000 Hz. The data for military and marching band music and traditional music genres were limited. The retrieved studies indicated a higher risk of hearing loss >20 dB in the frequency range of 4,000–6,000 Hz. A total of 17 studies adjusted the audiogram results for age, 2 did not, and 59 had no report. Data extraction yielded a prevalence of notch configurations in 20–50% of the classical musicians, with hearing loss affecting 5–70% of them. Up to 40% of rock, pop, and jazz musicians showed notch configurations, with 20–60% experiencing hearing loss.ConclusionOverall, a definitive assessment of the prevalence of musicians’ hearing loss cannot be drawn from the available data. Prospective, longitudinal studies with reliable sample sizes and representative populations are essential. A multicenter study would also be valuable.